2006
DOI: 10.1002/jmv.20677
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relatedness and genetic diversity of hepatitis B virus isolates in Eastern India

Abstract: Hepatitis B virus (HBV) has been classified into eight genotypes, and several subgenotypes, distinctly distributed geographically. The genotypes A and D were previously reported to be predominant in India. Recent studies indicated evidence of circulation of genotype C in Eastern part of India. With the aim to confirm the phylogenetic relation and molecular genetic characteristics of the HBV circulating in Kolkata, the most populous city in Eastern India, 11 strains were isolated and the complete genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 45 publications
6
85
1
Order By: Relevance
“…The forward and reverse sequences collected from the sequencer were checked and manually edited in the electro-pherograms using the SeqScape version 2.5 (Applied Biosystems) and MEGA5 software [12]. Genotyping was performed on the basis of phylogenetic relationship, taking 345 base pair sequences along with representative reference sequences from different sub genotypes as described earlier for hepatitis B virus [13,14]. Phylogenetic grouping using a bootstrap neighbour-joining (NJ) analysis with 1,000 replications was performed using the S gene sequence of HBV isolated from Nicobarese tribes and that of other representative sequences submitted in the NCBI database.…”
Section: Methodsmentioning
confidence: 99%
“…The forward and reverse sequences collected from the sequencer were checked and manually edited in the electro-pherograms using the SeqScape version 2.5 (Applied Biosystems) and MEGA5 software [12]. Genotyping was performed on the basis of phylogenetic relationship, taking 345 base pair sequences along with representative reference sequences from different sub genotypes as described earlier for hepatitis B virus [13,14]. Phylogenetic grouping using a bootstrap neighbour-joining (NJ) analysis with 1,000 replications was performed using the S gene sequence of HBV isolated from Nicobarese tribes and that of other representative sequences submitted in the NCBI database.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is not true for genotype D with subgenotypes D1, D2 and D3 being described as widespread in the world; e.g. D3 was found in Asia (East India) [40] , South Africa [41] and Europe (Serbia) (Stanojevic et al, unpublished results).…”
Section: Hbv Genotypes and Subgenotypesmentioning
confidence: 99%
“…HBV/C is associated with more severe liver diseases than HBV/ B (Kramvis et al, 2008;Sugauchi et al, 2004;Banerjee et al, 2006;Huy et al, 2006;Sakamoto et al, 2006) while contrary studies reported similarity on the risk of HCC development in either HBV/B or HBV/C infection (Kao et al, 2003;Sumi et al, 2003;Yuen et al, 2003Yuen et al, , 2009. Also, patients infected with HBV/D appear to have a higher incidence of HCC (Chan and Sung, 2006) whereas patients with either HBV/C or HBV/D have a lower response rate to treatment with IFN-α compared to those with HBV/A and HBV/B (Zollner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%